Presentation - Cornejo, Tomás; Lagos, Catalina; Chavarría Contreras, Rafael (Revista de Historia Social y de las Mentalidades, 2020)
This dossier aims to promote reflection and stimulate debate about the importance and meaning that archives have for historical practice. What do we mean by "archival work" that we assume is characteristic of our work? How is this currently conceptualized when we look at previously ignored practices? The articles comprising the dossier review experiences from various areas, regarding the use given to documentary heritage, the type of materials or mediums, and the processes of access, cataloging, and organization of the documents that enable their consultation and sharing with society